Штучне формування пагонової системи в інтродукованих видів родини ранникових (Scrophulariaceae Juss.) - Prokopchuk, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Results of researches of artificial formation of the sprout system in Antirrhinum majus L., Verbascum blattaria L. and Veronica longifolia L. for obtaining more compact plants with more intensive branching of the system of generative sprouts are presented.